Ebu'l-Huseyn el-Basrî'nin kıyas anlayışı - Ataş, Sacide (My University, 2017)
Bu çalışmada Ebu’l-Huseyn el-Basrî’nin kıyasın meşruiyetini temellendirme şekli, kıyasın şartları ve diğer tartışmalı konularla alakalı görüşleriortaya konmaya çalışılmıştır.

This dissertation I try to examine Abu al-Husayn al-Basrî's opinion about the way of his justification of legitimacy of qiyas, the stipulation of qiyas and the other debated topics about qiyas especially about the illa.
Keywords: al-Illa; al-Mu’tamad; Ebu’l-Huseyn el-Basrî; el-Mu’temed; Hukuk; İllet Abu al-Husayn al-Basrî; İslam dini; İslam hukuku; Kıyas; Legal Reasoning; Qiyas